Gelation Behavior of 5-Chloro-8-hydroxyquinoline, an Antituberculosis Agent in Aqueous Alcohol Solutions - Jukka Korpela; Hannu Salo; Erkki Kolehmainen (Antibiotics, 2012)
It was shown that 5-chloro-8-hydroxyquinoline, an antituberculosis agent, gels aqueous alcohol solutions efficiently. Thermal stability and gel-to-sol transition temperature of 1% gel in CD3OD/D2O (2:1) was studied by 1H-NMR. Fibrous structures of four xerogels have been characterized by scanning electron microscope.